2021
DOI: 10.3889/oamjms.2021.6529
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of Carica papaya Leaf Can Increase Breast Milk in Lactating Rat

Abstract: BACKGROUND: Carica papaya leaves (Carica papaya L) have been used empirically and traditionally as a galactogogue, but their mechanism as galactogogue is still unknown. AIM: This study aimed to analyze the effect of ethanol extract from papaya leaves on blood prolactin levels, prolactin receptor (prlr) gene expression, the number of breast alveoli and lobes of lactating rats. METHODS: This in vivo true experimental study with a post-test control group design was conducted on 24 rats with the same l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The previous study shows that papaya leaf ethanol extract can increase prolactin level in blood plasma, the prolactin receptor (prlr), the number of lobes and alveoli of mammae epithelial cell in lactating rats 37 . The increasing of prlr in mammary epithelial cells can induce ductal side branching, alveolar budding, and milk secretion through specific transcription factors such as STAT5 38 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The previous study shows that papaya leaf ethanol extract can increase prolactin level in blood plasma, the prolactin receptor (prlr), the number of lobes and alveoli of mammae epithelial cell in lactating rats 37 . The increasing of prlr in mammary epithelial cells can induce ductal side branching, alveolar budding, and milk secretion through specific transcription factors such as STAT5 38 .…”
Section: Discussionmentioning
confidence: 96%
“…Varghese's study showed that prlr internalization is dependent on K63 polyubiquitination of the receptor, whereas elevated PRL signaling would be promote the downregulation of prlr 58 . From the previous study, we know that administration of D3 also causes a decrease of prlr gene expression 37 . Thus, it will indirectly cause a decrese of β-casein (Csn2) gene expression, then a decrease of β-casein levels, total protein levels, and milk volume which unknown mechanism.…”
Section: Pharmaceutical Sciences Asiamentioning
confidence: 95%
“…However, papaya leaves contain flavonol components (kaempferol and quercetin), which positively aff ect phytoestrogens because they can activate prolactin receptors to increase milk production (Setyono et al, 2016). Table 6 summarized selected in vivo studies of papaya leaves as a galactagogue using lactating rats (Herawati et al, 2021) and humans (Ikhlasiah et al, 2020;Khasanah et al, 2021;Pratiwi, 2018). Herawati et al (2021) showed that papaya leaves ethanol extract significantly increased prolactin level, prolactin receptors gene expression, and the number of breast alveoli and lobules in lactating rats compared to the control.…”
Section: Papaya Leafmentioning
confidence: 99%
“…Table 6 summarized selected in vivo studies of papaya leaves as a galactagogue using lactating rats (Herawati et al, 2021) and humans (Ikhlasiah et al, 2020;Khasanah et al, 2021;Pratiwi, 2018). Herawati et al (2021) showed that papaya leaves ethanol extract significantly increased prolactin level, prolactin receptors gene expression, and the number of breast alveoli and lobules in lactating rats compared to the control. A dosage of 1.9 mg/200 g body weight/day of papaya leaves ethanol extract was the most eff ective treatment since it gave the highest increase.…”
Section: Papaya Leafmentioning
confidence: 99%
“…Based on the liquid chromatography mass spectroscopy (LCMS)/MS analysis, it is known that papaya leaves also contain flavonoids (unpublished data). An in vivo study has shown that papaya leaves can increase plasma prolactin levels in lactating rats [30]. This study aims to explain the molecular mechanism of active compounds from papaya leaves in regulating or influencing the production of the prolactin hormone using a docking technique as a tool for virtual screening and optimizing the combination of active compounds (ligands) with estrogen, leptin, and aromatase as the target proteins.…”
Section: Introductionmentioning
confidence: 99%